From the Rib to Human Unity: Paradigm Shifts in the Interpretation of Q. 4:1 in Indonesian Qur'anic Exegesis - Muhammad Naufal Hakim; Mokh. Fatkhur Rokhman; Jullul Wara; Abd. Kholid; Muflikhatul Khoiroh (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study examines the paradigm shift in the interpretation of Q. 4:1 within the corpus of Indonesian Qur’anic exegesis across historical landscape of Indonesian exegesis, an area that has not been systematically mapped using a theory-driven framework. Five primary works were selected as the objects of analysis: Tarjumān al-Mustafīd by ʿAlī al-Fansūrī, Marāḥ Labīd by Nawawī al-Jāwī, Tafsīr al-Azhar by Karim Amrullah, Tafsīr al-Mishbāh by Quraish Shihab, and Tafsir Kebencian by Zaitunah Subhan. Employing Thomas S. Kuhn’s paradigm shift theory and discourse analysis methods, this study identifies three key findings. First, the interpretation of Q. 4:1 has undergone a transformation from a theocentric paradigm, which views the creation of Ḥawwāʾ from Ādam’s rib as its theological basis, to an anthropocentric paradigm that grounds human unity in humanistic and egalitarian values. Second, this shift is also evident at the epistemological level, moving from classical to modern sources, from global to thematic methods, and from disciplinary to interdisciplinary approaches. Third, the paradigm transformation correlates directly with the exegetes' intellectual contexts: Alī al-Fansūrī and Nawawī al-Jāwī reflect traditionalism, Karim Amrullah and Quraish Shihab represent modernism, while Zaitunah Subhan embodies neomodernism. Overall, this study demonstrates that the paradigm shift in Qur’anic exegesis is not merely an exegetical phenomenon but also reflects broader epistemic and ideological transformations in Islamic thought which offer a critical lens for understanding the evolution of religious authority and social values.